Governmental Professional Development Initiatives for the Implementation of Language Policies and Curriculum Guidelines : Secondary School Teachers’ Experiences, Challenges and Views (2020)
ABSTRACT: A case study was conducted to explore public secondary school teachers’ perspectives, practices, and experiences concerning the design and implementation of the English curriculum, as well as the professional development offered by the government in order to implement language policies and curriculum guidelines in the city of Medellin, Colombia. The study lasted one year and included a survey, the analysis of curriculum documents from five selected institutions, and focus group interviews as data collection instruments. Results indicate that the initiatives provided by the government have not been effective in supporting teachers in this endeavor as they have been very limited in terms of curriculum design, and reflect a technical view of teacher learning. In addition, several contextual and social factors have tremendously affected the implementation of language policies and curriculum guidelines in schools. Besides, teachers point to several needs, including that they have more time to appropriate and implement reforms, that they be included in policy-making as affected parties, that professional development initiatives be freed from political and economic interests and that they be offered a preparation that combines improving their language proficiency, English teaching methodologies and curriculum design.